From Onomatodoxy to Aesthetics: Aleksei Losev's Concept of Symbol - Obolevitch, Teresa, (Contemporary Russian Philosophy ;, 2025)
In From Onomatodoxy to Aesthetics: Aleksei Losev's Concept of Symbol , Teresa Obolevitch analyzes the category of symbol in broad historical and philosophical context, with a focus on Losev's exploration of symbol over his prolific and tragic career. A survivor of the Stalinist camps, Losev is recognized as the "last classic" of Russian Silver Age philosophy. This book addresses Losev's critical role within the divisive debate over onomatodoxy (imiaslavie), or the divine name, which occupied the minds of Russian thinkers in the early nineteenth century. Obolevitch presents the ancient and patristic roots of onomatodoxy and elucidates its importance for Losev's work in a range of fields, including aesthetics, mathematics, philosophy of language, and religion. Losev's work revolves around the possibility of expressing reality in language and his conception of symbol reflects both the apophatic aspect of Logos, as well as the possibility for new interpretations of reality.